Southern thought, islandness and real-existing degrowth in the Mediterranean. (September 2022) - Kallis, Giorgos; Varvarousis, Angelos; Petridis, Panos
Highlights: Degrowth signifies an alternative to the prevalent model of growth-based development. This paper charts a research agenda on real-existing degrowth. The cultural geography of small islands provides fertile context for degrowth. 'Southern thought' revalorizes what otherwise would be seen as backwardness and under-development. Abstract: In thinking about alternatives to growth-based development, we draw attention to Mediterranean islands and the way they animate imaginaries and practices of a simple life. We follow Franco Cassano's thesis of 'Southern thought' – a critique of Western developmentalism, prioritizing instead values of slowness, moderation and conviviality. These values are central to what Serge Latouche and others call 'degrowth'. Drawing on fieldwork and ethnography from Ikaria and Gavdos, two remote islands in the Greek archipelago, we show how Southern thought, and forms of real-existing degrowth develop in relation to 'islandness' – a physical and cultural condition specific to small islands. Geography, historical contingency, and processes of myth-making combine to re-valorise what otherwise would be seen as 'undeveloped' places, thereby generating space for real-existing degrowth.